PENGEMBANGAN PERANGKAT PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Mahlianur rahman (Universitas Syiah Kuala, 2022)
This study aims to (1) produce a SETS kit that is feasible to the creative thinking of Elementary School (2) find out the effectiveness of the SETS kit to the creative thinking. This study is a research and development refering to the opinion of Borg Gall. The design of learning kits consists of 9 steps, including (1) research and information collection; (2) planning; (3) developing preliminary form of draft product; (4) preliminary field testing; (5) main product revision; (6) main field testing; (7) operational product testing; (8) operational field testing; and (9) final product revision. Subjects were students of Elementary School 3 Kota Fajar. The results show that the learning kit is effective to creative thinking of students according to the material expert and learning expert with excellent ratings category. Based on the result show that there are significant differences in creative thinking of students who take the study with SETS kits with those who do not use learning kits.